2020
DOI: 10.2116/analsci.20p229
|View full text |Cite
|
Sign up to set email alerts
|

Paper-based Chemiluminescence Device with Co-Fe Nanocubes for Sensitive Detection of Caffeic Acid

Abstract: In this work, a new chemiluminescence (CL) system of Co-Fe prussian blue analogs nanocubes (Co-Fe PBA NCs) which can catalyze luminol to produce strong CL in the absence of H2O2 was established. Co-Fe PBA NCs has the property of oxidase-like activity and it can catalyze the generation of active oxygen radicals in the dissolved oxygen system. Since caffeic acid (CA) can remove reactive oxygen species in the system, a sensitive detection method for CA on the paper-based chip was developed.Under the optimal condi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 38 publications
0
6
0
Order By: Relevance
“…22 The bands at 2118 cm −1 and 2029 cm −1 are related to the Co( ii )–NC–Fe( iii ) and Co( ii )–NC–Fe( ii ) species, respectively, signifying the nature of the CN bond in the molecule. 23,24 The morphology was studied by SEM and TEM. In the SEM image shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…22 The bands at 2118 cm −1 and 2029 cm −1 are related to the Co( ii )–NC–Fe( iii ) and Co( ii )–NC–Fe( ii ) species, respectively, signifying the nature of the CN bond in the molecule. 23,24 The morphology was studied by SEM and TEM. In the SEM image shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…S2 (ESI†) that compared with the blank group, the absorbance at 652 nm decreases successively with the increase in IPA, SOD or histidine concentration, suggesting that O 2 ˙ − , ˙OH, and 1 O 2 are active intermediate species during the catalytic process, which is consistent with the previous report. 24…”
Section: Resultsmentioning
confidence: 99%
“…The dual mode detection (FL and CL) was achieved with the LODs of 0.3 ng/mL for CL and 0.2 ng/mL for FL. In 2021, it was reported that by using Co-Fe Prussian blue analogue nanocubes (Co-Fe PBA NCs), the strong CL still happened in the absence of H 2 O 2 on a paper-based CL device [ 286 ].…”
Section: Optical Detection Methodsmentioning
confidence: 99%
“…(B) Determination of caffeic acid in tea samples by a CoFePBA-based chemiluminescence system. Reprinted with permission from ref . Copyright 2020, The Japan Society for Analytical Chemistry.…”
Section: Biosensormentioning
confidence: 99%